ГУМАНИТАРНАЯ ЭКСПЕРТИЗА И СОЦИАЛЬНАЯ ВЕРИФИКАЦИЯ ТЕОРЕТИЧЕСКИХ КОНСТРУКТОВ В ПОСТАКАДЕМИЧЕСКОЙ НАУКЕ - Косова, Ю. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
Предметом анализа являются трансформационные процессы познания в постакадемической (по-стнеклассической) науке. Результатом социальной верификации в обозначенных областях знания явля-ется появление верификационного концепта, который в результате трансформации приобретает видсамореализующегося/самотормозящегося прогноза.Косова Ю.В. Гуманітарна експертиза та соціальна верифікація теоретичних конструктів в по-стакадемічній науці. Предметом аналізу є трансформаційні процеси пізнання в постакадемічній(постнекласичній) науці. Результатом соціальної верифікації в зазначених областях знання є появаверифікаційного концепту, який в результаті трансформації набуває вигляду прогнозу, що самостійнореалізується або само гальмується.Ключові слова: соціальна верифікація, гуманітарна експертиза, прогноз, що самостійно реалізу-ється або самогальмується, постакадемічна наука.Kosova Yu.V. Humanitarian Expertise and Social Verification of the Theoretical Constructs inPostacademical Science. As the modern science acquired the human dimension the process of scientific cognitionbecomes dependent on the cultural context. It inevitably leads to the incorporation of the valuation componentinto the content of the scientific theory, that is, the inclusion of social verification in the general scheme oflogical and empirical verification. It becomes especially evident in the trance discipline areas of scientific knowledge.The result of social verification in the indicated areas of knowledge is the emergence of verificational concept,in the process of transformation it becomes a self-fulfilling/selfbraking forecast. Humanitarian expertise isengaged in prediction of such verification, this expertise acts as a socio-humanitarian equivalent for logical verificationas an attribute of classical science and aims at identifying the social risks connected with the creationand implementation of new technologies. We focus our attention at the phenomena that are caused by the «invasion» of social-cultural context into the procedure of confirmation of validity and reliability of the scientific concepts,- humanitarian expertise of natural-scientific theories and non-linear dependence of the result of the actualizationof the epistemological procedures of the verification/falsification from the results of such expertise.Keywords: social verification, humanitarian expertise self-fulfilling/selfbraking forecast, post-academicalscience.